THE RELATIONSHIP BETWEEN RESILIENCE WITH CONTINUANCE COMMITMENT OF HONORER TEACHER IN UPTD PENDIDIKAN KECAMATAN BANYUMANIK SEMARANG - Satriyo Dwi Atmoko; Anita Listiara (Jurnal EMPATI, 2012)
One way to be appointed as candidate of government employees was working as a honorer teachers. A people must remain in organization because he or she needs the salary and benefits and cannot find another job is called commitment continuance.This study aimed to determine the relationship between resilience with continuance commitment, and also to determine the effective contribution of resilience for continuance commitment in a honorer teacher.The population according to the characteristics of the study amounted is 102 honorer teachers in UPTD Kecamatan Banyumanik Semarang. Collecting data using a resilience scale consists of 30 items (α=0,946), and a continuance commitment scale consists of 19 items (α=0,888). The test ressult of hypothesis show that resilience has negative correlation with continuance commitment that show in rxy = -0,432 with level of significant correlation is 0,000 (p<0,05). The test results obtained for the coefficient of determination is 0,187. It is mean resilience of honorer teacher influence for 18,7% with continuance commitment. While 81,3% of continuance commitment is influenced by other factors outside the study variables. These factors include a individual predisposition, satisfaction with life, job expectations, organizational fit, perception of fairness, coworkers, stressors, and the job itself.